Survival of patients with alcohol diagnosis discharged from an emergency department: A population based cohort study - Anna Steinunn Gunnarsdóttir 1983- (2014)
Objectives: The aim was to study the cause specific mortality of users of emergency department (ED) who received a diagnosis of alcohol use disorder in comparison with mortality of all other users of the department, while taking into consideration other mental diseases and the frequency of visits. Methods: The study was a prospective cohort study of all individuals attending, and who were subsequently discharged home from the ED at Landspitali - the National University Hospital of Iceland (LUH) during the years 2002 to 2008. We followed-up 107 237 patients by record linkage to a nation-wide cause of death registry. Altogether 1 210 patients were ever with alcohol use disorders (ICD-10 codes F10) as the main diagnosis and 106 027 were never with that diagnosis. Every visit (n=257 955) was filed with unique registration number, patients identification number, birth date, gender, date of visit, and discharge diagnosis. Death rates among patients who had received an alcohol diagnosis were compared with death rates among patients who had never received such a diagnosis, with hazard ratio (HR) and 95% confidence intervals (CI) in Cox model, adjusted for age, gender, mental and behavioural disorders, year of entrance, and number of visits to the ED. Results: The adjusted HR for all causes of death for those who had received an alcohol diagnosis at the ED compared to those who had never received such a diagnosis was 1.91 (95%CI 1.51-2.42). The HR for alcohol use disorders was 47.68 (95%CI 11.56-196.59), and for alcohol liver disease the HR was 19.06 (95%CI 6.07-59.87). The HR was also elevated for diseases of the circulatory system 2.52 (95%CI 1.73-3.68), and external causes of injury and poisoning 4.02 (95%CI 2.48-6.53) mainly due to accidental poisoning (HR=13.64, (95%CI 3.98-46.73)), suicide (HR=2.72 (95%CI 1.08-6.83)), and event of undetermined intent (HR=10.89 (95%CI 4.53-26.16)). The HR for all causes of death was significantly associated with gender, age, year of entry, mental diseases, and frequency of visits to ...